The effect of one nostril inhalation, added to standard physiotherapy management, on hospital length of stay and pulmonary complications in patients with thoracic trauma: a randomised trial - Tootla, Sameer (University of the Witwatersrand, Johannesburg, 2024)
Background: Trauma is the second most common cause of mortality in South Africa. Thoracic trauma encompasses a wide variety of injuries that contributes to morbidity and mortality. It can vary from a simple blunt injury to complex penetrating injuries. South Africa has a high prevalence of thoracic injury, indicating a significant burden. Physiotherapists play an important part in the management of patients with thoracic trauma to reduce pain, prevent pulmonary complications, and improve physical function. One nostril inhalation (ONI) is a type of resistance breathing with limited use in physiotherapy clinical practice. Its function is to decrease inspiratory flow and rate and regain breathing control for patients who are experiencing pain. Objectives: To describe the profiles (demographic and clinical) of patients who sustained thoracic trauma and were admitted to the trauma wards at Chris Hani Baragwanath Academic Hospital. To investigate the effects of ONI, added to standard physiotherapy management of patients with thoracic trauma, on their primary (hospital length of stay and incidence of pulmonary complications) and secondary (level of pain, functional status, exercise capacity and rate of adverse events) clinical outcomes. Design: A single-centre, single-blinded, randomised trial was conducted. Methods: Potential participants were recruited from CHBAH trauma wards through consecutive sampling and written informed consent was obtained. Participants were allocated to one of two groups through 1:1 allocation using a computer-generated randomisation sequence. Group one received standard physiotherapy care and group two received standard physiotherapy plus ONI. Participants in group two performed ONI under supervision during physiotherapy treatment sessions and were also instructed to perform ONI independently every second waking hour and when experiencing pain. The ONI technique was taught as slow and deep inspirations with the mouth and one nostril closed by hand. The participant was informed to perform sets of 10 deep breaths every second waking hour of the day and, in addition, when experiencing pain. Their training was recorded in their given ONI diary. Re- enforcement of the ONI technique was done each day by the treating physiotherapist reminding the participant to continue the technique and to document in the ONI diary when it was done. Participants’ hospital length of stay, and incidence of pulmonary complications was recorded. Pain, physical function, exercise capacity and rate of adverse events was assessed on days 1, 3, 5, 7, 10, 15, 20, 25, and 30 or until hospital discharge. Patient recruitment started in April 2022 and was concluded in May 2023. Descriptive statistics were used to summarise the data and inferential statistics were used for group comparisons. Significance was reported as p-value <0.05. iii Results: One hundred and fifty participants (mean age 32.6 (SD 8.1); group one mean age 31.4 (SD 7.4); group two mean age 33.9 (SD 8.6)) were recruited from the trauma wards. The groups were comparable as no significant between group differences for demographic and clinical characteristics existed at baseline. Majority were male (n=139, 93%). Majority had penetrating thoracic trauma (n=120, 80%) while others had blunt thoracic trauma (n=30, 20%). The most common cause of thoracic trauma was assault (n=124, 83%). In group one, 84% (n=63) had no rib fractures, 12% (n=9) had 1-3 ribs fractured on the left side, 4% (n=3) had 1- 3 ribs fractured on the right side. No participants who had more than 3 ribs fractured bilaterally. In group 2, 76% (n=57) had no rib fractures, 18.7% (n=14) had 1-3 ribs fractured on the left side, 4% (n=3) had 1-3 ribs fractured on the right side and 1.3% (n=1) had more than 3 ribs fractured bilaterally Fifty-eight percent (n=82) participants had a unilateral pneumothorax and 43% (n=64) had a unilateral haemo-/haemopneumothorax. Almost all participants (n=149, 99%) were managed with an intercostal drainage system. The ONI group had a significantly longer length of stay (0.49 days) (p-value 0.008) than the standard care group. None of the participants in either group developed pulmonary complications during their hospital stay. Pain decreased for both groups over time and was not significantly different between groups. There were no significant differences in the functional outcomes assessed (FSS-ICU mobility scale, 10-meter walk test and the TUG test) and the exercise capacity (one-minute sit to stand test) between group 1 (standard treatment) and group 2 (ONI). There were, however, gradual improvements in both the functional outcomes and exercise capacity through the days of assessment in both groups. There were no reports of adverse events that occurred during physiotherapy sessions for both group 1 (standard treatment) and group 2 (ONI). All the participants in group 1 (standard treatment) and group 2 (ONI) were discharged home, with none requiring a follow up outpatient appointment, according to the treating physiotherapists. Conclusion: The findings from this study suggest that ONI added to standard physiotherapy management in patients with thoracic trauma does not influence clinical outcomes.
A research report submitted in fulfillment of the requirements for the Master of Science in Physiotherapy, in the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; blunt thoracic trauma; penetrating thoracic trauma thoracic trauma/injury; thoracic trauma; physiotherapy for thoracic trauma; pneumonia; atelectasis; lung compliance; pneumothorax; haemothorax; anatomy of the thoracic wall; pain; breathing; one nostril inhalation; one nostril breathing and physiology of thoracic trauma; SDG-3: Good health and well-being